2011
DOI: 10.3724/sp.j.1005.2011.01327
|View full text |Cite
|
Sign up to set email alerts
|

T-DNA integration patterns in transgenic plants mediated by <I>Agrobacterium tumefaciens</I>

Abstract: The genetic transformation mediated by Agrobacterium tumefaciens has been widely applied to research of transgenic plants. As the vector of the exotic genes, the integration patterns of T-DNA fragments affects not only transformation efficiency and stability, but also expression properties of the transgenes. This review summaries the two major patterns and the rules of T-DNA integration in Agrobacterim-mediated transformation, rules of T-DNA mediated by Agrobacterium tumefaciens, as well as research tools for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…This method does not require laborious preparations and the use of radioactive probes in DNA hybridizations. Although the method was only recently developed (Liu and Chen, 2007;Yang et al, 2011), primer design appears to be crucial for eliminating nonspecific PCR bands. For example, we obtained the same flanking sequence (alpha tubulin 5) from a transformant line using 3 different AD primers.…”
Section: Discussionmentioning
confidence: 99%
“…This method does not require laborious preparations and the use of radioactive probes in DNA hybridizations. Although the method was only recently developed (Liu and Chen, 2007;Yang et al, 2011), primer design appears to be crucial for eliminating nonspecific PCR bands. For example, we obtained the same flanking sequence (alpha tubulin 5) from a transformant line using 3 different AD primers.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are associated with stresses such as wounding and osmotic stress, and GM plants obtained through tissue culture are more variable than those obtained using the floral‐dip technique (Montero et al, 2011). Agrobacterium and other pathogen infections may also cause mutations (Yang et al, 2011). In total, many factors can induce unintended effects, including random mutations, somatic mutations, gene sequence insertions, positional effects, inductive effects, mutations in the tissue culture process, and pleiotropy, which may emerge at any stage of the GE plant development process (Wang et al, 2019) (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Two RNAi‐based GE rice lines (Ubi5 and Ubi6) were transformed with the same transformation vector, which included promoters derived from ubiquitin genes and IR sequences; however, no hpt marker genes were present. Yang et al (2011) found that the insertions of the Ubi5 and Ubi6 constructs were located in an intergenic site at 26.82 and 7.69 Mb on chromosome 6, respectively (unpublished), and each as a single copy. The researchers further verified this insertion site via PCR using three specific PCR primers (China patent: CN201911243983.0).…”
Section: Methodsmentioning
confidence: 99%